Artemisinin attenuated oxidative stress and apoptosis by inhibiting autophagy in MPP(+)-treated SH-SY5Y cells - Yan, Junqiang (J Biol Res (Thessalon), 2021)
BACKGROUND: Parkinson’s disease (PD) is the second most common neurodegenerative disease after Alzheimer's disease. The oxidative stress is an important component of the pathogenesis of PD. Artemisinin (ART) has antioxidant and neuroprotective effects. The purpose of this study is to explore the neuroprotective effect of ART on 1-methyl-4-phenyliodine iodide (MPP (+))-treated SH-SY5Y cells and underlying mechanism. METHODS: We used MPP(+)-treated SH-SY5Y cells to study the neuroprotective effect of ART. Cell viability was measured by MTT assay after incubating the cells with MPP(+) and/or ART for 24 h. DCFH-DA was used to detect the level of intracellular reactive oxygen species (ROS), and WST-8 was used to detect the level of superoxide dismutase (SOD). The level of intracellular reduced glutathione (GSH) was detected with 5,5΄-dithiobis-(2-nitrobenzoic acid), and the level of malondialdehyde (MDA) was assessed based on the reaction of MDA and thiobarbituric acid. A mitochondrial membrane potential detection kit (JC-1) was used to detect changes in the mitochondrial membrane potential (MMP), and an Annexin V-FITC cell apoptosis kit was used to detect cell apoptosis. The expression levels of caspase-3, cleaved caspase-3 and the autophagy-related proteins LC3, beclin-1, and p62 were detected by Western blotting. In addition, to verify the change in autophagy, we used immunofluorescence to detect the expression of LC3 and p62. RESULTS: No significant cytotoxicity was observed at ART concentrations up to 40 μM. ART could significantly increase the viability of SH-SY5Y cells treated with MPP(+) and reduce oxidative stress damage and apoptosis. In addition, the Western blotting and immunofluorescence results showed that MPP(+) treatment could increase the protein expression of beclin1 and LC3II/LC3I and decrease the protein expression of p62, indicating that MPP(+) treatment could induce autophagy. Simultaneous treatment with ART and MPP(+) could decrease the protein expression of beclin1 and LC3II/LC3I and increase the protein expression of p62, indicating that ART could decrease the level of autophagy induced by MPP(+). CONCLUSION: Our results indicate that ART has a protective effect on MPP(+)-treated SH-SY5Y cells by the antioxidant, antiapoptotic activities and inhibition of autophagy. Our findings may provide new hope for the prevention and treatment of PD.